Efforts to Improve Postpartum Maternal Behavior through Family-Centered Maternity Care (FCMC) about Postpartum Care Education - Candra Wahyuni (Universitas STRADA Indonesia, 2024)
The role of parents is inseparable from the participation or cooperation between the mother and the family (husband) and other family members. An obstacle that is still found in the care of postpartum mothers is the assumption that postpartum mothers are sick mothers, their mobilization is inhibited, the type of food is restricted, the provision of colostrum breast milk is inhibited so that the needs of postpartum mothers are prioritized for full rest. The involvement of extended families in the care of babies has so far been misinterpreted, where the care of babies is left to other family members. After efforts to improve the behavior of postpartum mothers through Family Centered Maternity Care (FCMC) education, it is hoped that postpartum mothers can carry out postpartum care by involving the family. Implementation method with demonstration and discussion. The media used are baby phantoms, postpartum care booklets, LCDs, Laptops, and Projectors. The implementation of health education is carried out by visiting the home of postpartum mothers. The result of community service is that 90% of postpartum mothers can do postpartum care with family involvement. As well as from the results of monitoring and evaluation by way of meeting again by conducting home visits (home care) to postpartum mothers using instruments related to postpartum care. Based on the implementation of community service, it can be concluded that there is an increase in the behavior of postpartum mothers in postpartum care.